HMGB1 in Pediatric COVID-19 Infection and MIS-C: A Pilot Study - Petrarca, Laura; Manganelli, Valeria; Nenna, Raffaella; Frassanito, Antonella; Ben David, Shira; Mancino, Enrica; Garofalo, Tina; Sorice, Maurizio; Misasi, Roberta; Midulla, Fabio (Frontiers in Pediatrics, 2022)
Objective Since the beginning of the coronavirus disease 2019 (COVID-19) pandemic, a novel syndrome known as a multisystem inflammatory syndrome in children (MIS-C) was reported in previously healthy children. A possible pro-inflammatory molecule, high-mobility group box 1 (HMGB1), may be assumed to play an important role in the pathogenesis and clinical presentation of MIS-C. We described the clinical picture of patients with MIS-C and we also aimed to test and compare HMGB1 serum levels of MIS-C patients with those of patients with previous SARS-CoV2 infection and healthy children. Study design We determined HMGB1 levels by Western blot in 46 patients and divided them into three groups, namely, five patients with MIS-C (median age: 8.36 years), 20 children with a history of SARS-CoV-2 infection (median age: 10.45 years), and 21 healthy children (controls) (median age: 4.84 years), without evidence of respiratory infection in the last 3 months. Results The median level of HMGB1 in the serum of five patients with MIS-C was found to be significantly higher compared with both patients with a recent history of COVID-19 (1,151.38 vs. 545.90 densitometric units (DU), p = 0.001) and control (1,151.38 vs. 320.33 DU, p = 0.001) groups. The HMGB1 level in MIS-C patients with coronary involvement had a slightly higher value with respect to patients without coronary dilatation (1,225.36 vs. 1,030.49 DU, p = 0.248). In two of the five children with MIS-C that performed a follow-up, the HMGB1 value decreased to levels that were superimposable to the ones of the control group. Conclusion The significantly high level of HMGB1 protein found in the serum of COVID-19 and patients with MIS-C supports its involvement in inflammatory manifestations, suggesting HMGB1 as a potential biomarker and therapeutic target in patients with severe illness.